Estudo do desempenho térmico de concretos com ar incorporado - Cintra, Arthur Moura (2015)
The use of concrete walls in single-family buildings had greatly increased in recent years. To meet the demand of housing construction of social interest and the need to improve performance, business construction have sought new construction systems being one of them the walls of reinforced concrete with self compacting concrete or entrained air. The evolution of the use of concrete walls culminated in the publication, in May 2012, the NBR 16055. The purpose of this paper is to present the results of a survey on the actual performance of air incorporated into plates, considering the climatic variations of the period winter. The control variable is the heat conduction gradient, aiming the thermal performance of housing. The experimental program consisted of performing panels 16 (quantity determined by ANOVA), and reference 4 and 4 for each dose developer air additive (0.04%, 0.08% and 0.12% on the cement consumption ). The thermal test was conducted in a chamber with two thermally insulated compartments and independent control of temperature (10 oC to 25 oC) and relative humidity. The partition between the two compartments the plates were placed. They determined the physical properties in fresh and hardened specimens and the behavior of each group with respect to thermal conduction. For the percentage of additive used, the total air content ranged from 2.8% to 11.88% and the frustoconical rebate increased from 21 mm to 107 mm. The results showed that the density decreased to 11% when incorporated additive. The compressive strength had reductions of up to 53% at 28 days of age and the modulus of elasticity also reduced by 26%. In the thermal test, with a chamber ranging from 10 ° C to 25 ° C and maintained at 10 ° C another, the concrete with additive was 0.04% with a temperature of approximately 1.5 ° C lower than the reference concrete.